Synthesis of Mg1.5Mn0.75Ti0.5O4 and Its Li+ Extraction/Insertion Reaction in the Aqueous Phase - Wang, Lintong; Jiang, Jinhe (Asian Journal of Chemistry, 2013)
Inverse spinel-type metal oxides, magnesium-manganese-titanium oxide (Mg1.5Mn0.75Ti0.5O4), was prepared by a solid state reaction crystallization method. This material was investigated by X-ray, saturation capacity of exchange and Kd measurement. The experimental results have proved that the acid-treated sample has a capacity of exchange 11.1 mmol g-1 for Li+ in the solution, the chemical analysis showed that the Li+ extraction/insertion progressed mainly by ion-exchange mechanism and surface adsorption.